2012
DOI: 10.1016/j.aap.2011.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of an identification system in construction site safety for proactive accident prevention

Abstract: Citation: YANG, H. ... et al, 2012. Design and implementation of an identification system in construction site safety for proactive accident prevention. Accident Analysis and Prevention, 48, Additional Information:• This is the author's version of a work that was accepted for publication in the journal Accident Analysis & Prevention. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 45 publications
0
37
0
2
Order By: Relevance
“…To prevent falling and proximity accidents at construction sites, Wu et al [26,27] investigated the application of ZigBee/RFID sensor network technology. In a similar study, Yang et al [28] proposed a safety management system based on a ZigBee-enabled wireless sensor network and RFID technology. Kelm et al [29] proposed an RFID-based automatic identification system that allows compliance checking of the personal protective equipment (PPE) worn by workers at construction sites.…”
Section: Review Of Proximity Warning Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent falling and proximity accidents at construction sites, Wu et al [26,27] investigated the application of ZigBee/RFID sensor network technology. In a similar study, Yang et al [28] proposed a safety management system based on a ZigBee-enabled wireless sensor network and RFID technology. Kelm et al [29] proposed an RFID-based automatic identification system that allows compliance checking of the personal protective equipment (PPE) worn by workers at construction sites.…”
Section: Review Of Proximity Warning Technologymentioning
confidence: 99%
“…Past research has shown the applicability of RFID technology for accident prevention [25][26][27][28][29]37]. The RFID system is a technology that identifies objects using radio waves of different frequencies.…”
Section: Research Motivation and Scopementioning
confidence: 99%
“…Multiple other technologies have been studied and evaluated including vision cameras [12][13], radio detection and ranging (RADAR) [14], radio-frequencyidentification (RFID) [11,[15][16], ultra wideband (UWB) [17][18], range imaging cameras [19][20][21], and global positioning system (GPS) [22][23] for potential deployment in the construction environment. Although some of these systems were capable of detecting and alerting workers in real-time of hazards, many are infrastructure-heavy as they require expensive setup of sensing infrastructure.…”
Section: Hazardous Proximity Situationsmentioning
confidence: 99%
“…Wireless sensor networks (WSNs) have the advantages of low cost, flexible deployment, and so forth and have been widely used in varied fields, such as environmental monitoring [1,2], intelligent control [3], and military reconnaissance [4,5]. In WSNs, energy efficiency is very important and also a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…(1) We have analyzed the influencing factors of energy consumption based on the hexagonal structure [3] and deduce the internal laws between the number of nodes and the area energy consumption ratio.…”
Section: Introductionmentioning
confidence: 99%